2018
DOI: 10.1103/physrevb.98.035420
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation energy, quasiparticle band structure, and excitonic properties of selenium and tellurium atomic chains

Abstract: Effects that are not captured by the generalized-gradient density-functional theory play a prominent effect on the structural binding, and on the electronic and optical properties of reduceddimensional and weakly-bound materials. Here, we report the exfoliation energy of selenium and tellurium atomic chains with non-empirical van der Waals corrections, and their electronic and optical properties with the GW and Bethe-Salpeter formalisms. The exfoliation energy is found to be within 0.547 to 0.719 eV/u.c. for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 61 publications
(84 reference statements)
6
25
0
Order By: Relevance
“…Studies on many-electron effects of similar structures, such as 1D Se, have been reported recently. [55] The DFT-calculated and quasiparticle energy band structures of the isolated chain Te without SOC are plotted in Fig. 4(a).…”
Section: Chain Tementioning
confidence: 99%
See 1 more Smart Citation
“…Studies on many-electron effects of similar structures, such as 1D Se, have been reported recently. [55] The DFT-calculated and quasiparticle energy band structures of the isolated chain Te without SOC are plotted in Fig. 4(a).…”
Section: Chain Tementioning
confidence: 99%
“…The e-h binding energy of the lowest-energy E 1 exciton is about 2.40 eV, which is comparable with that of the chain Se (2.77 eV) and significantly surpasses that (0.67 eV) in monolayer Te. [55] A very large exciton binding energy of 3.5 eV was calculated in the BN chain. [9] Our further analysis shows that the E 1 exciton is from the interband transitions between the first, second, and third highest valence bands and the first…”
Section: Chain Tementioning
confidence: 99%
“…According to values reported in the literature, trigonal selenium exhibits a band gap energy value of 2 eV. 13 , 57 , 58 Although a higher energy gap is expected in quantum dots due to confinement effects, a slight decrease in band gap is observed in t-Se QDs. This can be attributed to the presence of surface states and traps.…”
Section: Resultsmentioning
confidence: 88%
“…Also, composite materials constituted by a dielectric material sandwiched between two t-phases can offer functionalities for tunneling devices. As a final remark, 3D crystals, multilayer, bilayer and monolayer, and 1D chain structures [58][59][60][61] of Se and Te elements can reconstruct to form diverse structures with unusual properties under strain, thermal and optical excitations, excess charge and electric field.…”
Section: Discussionmentioning
confidence: 99%